Microstructure evolution and recrystallization behavior of two nickel-based single crystal superalloys - XU Fuze; LIN Yongcheng; MA Dexin; HE Daoguang; ZHAO Yunxing; LI Lyu; CHENG Bowen; DENG Yangpi (Cailiao gongcheng)
This study focuses on the single crystal （SC） superalloys CMSX-4 and DD5， designing and fabricating a SC test plate casting with five distinct stages. Castings with the same crystal orientation are selected to investigate their recrystallization （RX） behavior after solution heat treatment at 1300 ℃ for 2 h and 1310 ℃ for 4 h. The results indicate that CMSX-4 exhibits a stronger tendency for RX compared to DD5. Following a solution heat treatment at 1300 ℃， the CMSX-4 SC test plate displayed RX at the lower corners of 2-5 stage platforms， with the extent of RX expanding as the solution heat treatment temperature rose. Conversely， no RX was detected in the DD5 SC test plate post-treatment at 1300 ℃. Elevating the solution temperature to 1310 ℃ results in only a minor area of RX on the outer platform of the fourth stage in the DD5 SC test plate. The micro-shrinkage porosity and eutectic content of the as-cast and solution heat treated CMSX-4 alloy are both higher than those of the DD5 alloy. The higher content of eutectic and micro-shrinkage porosity provides more nucleation sites and quantities for RX in the CMSX-4 alloy， while the solution heat treatment temperatures above the γ' phase dissolution temperature weakens the pinning effect of coarse γ' phase on RX growth， and high melting point carbides and residual eutectic become important factors hindering RX growth. In addition， the high content of Co element reduces the stacking fault energy of the CMSX-4 alloy， making it with a high recrystallization tendency.